Fixed-angle plates in patella fractures - A pilot cadaver study - Wild, M.; Thelen, S.; Jungbluth, Pascal; Miersch, D.; Windolf, J.; Hakimi, M.; Betsch, Marcel (European Journal of Medical Research, 2011)
Objective: Modified anterior tension wiring with K-wires and cannulated lag screws with anterior tension wiring are currently the fixation of choice for patellar fractures. Failure of fixation, migration of the wires, postoperative pain and resulting revision surgery, however, are not uncommon. After preliminary biomechanical testing of a new fixed-angle plate system especiaUy designed for fixation of patella fractures the aim of this study was to evaluate the surgical and anatomical feasibility of implanting such a plate-device at the human patella. Methods: In six fresh unfixed female cadavers without history of previous fractures around the knee (average age 88.8 years) a bilateral fixed-angle plate fixation of the pateUa was carried out after previous placement of a transverse central osteotomy. Operative time, intraoperative problems, degree of retropatellar arthritis (following Outerbridge), quality of reduction and existence of any intraarticular screw placement have been raised. In addition, lateral and anteroposterior radiographs of all specimens were made. Results: Due to the high average age of 88.8 years no patella showed an unimpaired retropatellar articular surface and all were severely osteoporotic, which made a secure fixation of the reduction forceps during surgery difficult. The operation time averaged 49 minutes (range: 36-65). Although in postoperative X-rays the fracture gap between the fragments was still visible, the analysis of the retropatellar surface showed no residual articular step or dehiscence > 0.5 mm. Also in a total of 24 inserted screws not one intraarticular malposition was found. No intraoperative complications were noticed. Conclusions: Osteosynthesis of a medial third patella fracture with a bilateral fixed-angle plate-device is surgically and anatomically feasible without difficulties. Further studies have to depict whether the bilateral fixed-angle plate-osteosynthesis of the patella displays advantages over the established operative procedures. © I. Holzapfel Publishers 2011.
CRIS-Team Scopus Importer:2022-07-20
Keywords: Angle-stable plate; Feasibility study; Fixed-angle plate; Knee; Patella fracture